SOCIAL SUPPORT IS RELATED TO OPTIMISM FOR BREAST CANCER PATIENT RECOVERY - Sembiring, Erika Emnina; Pondaag, Ferlan Pondaag Ansye; Natalia, Adriani (Prodi Ilmu Keperawatan, Fakultas Ilmu Kesehatan, UIN Syarif Hidayatullah Jakarta, 2025)
Breast cancer is a malignancy with a high number of cases compared to other types of cancer. Breast cancer has a serious impact on the patient's psychology, namely decreased feelings of pride, feelings of sadness, anxiety, depression and not being ready to accept the condition of the disease they are experiencing. Breast cancer and psychological problems experienced by patients can reduce optimism for recovery. Optimism is influenced by social support, where social support makes breast cancer patients have the enthusiasm to recover, feel cared for, and feel like they are not alone in facing their disease. The aim of the research was to determine the relationship between social support and optimism for the recovery of breast cancer patients at RSUP Prof. DR. R.D Kandou. This research is a quantitative study with a cross sectional approach where the sample size is 61 breast cancer patients. Data analysis used the Spearman Rank test. The research results showed that most of the social support received by breast cancer patients was in the high category, namely 75.4%, and optimism for recovery was in the high category, namely 65.6%. Social support has a significant relationship with optimism for recovery in breast cancer patients with a value of p = 0.0001 and r = 0.548. The results of this research are a source of information in providing comprehensive nursing care to breast cancer patients while undergoing care and treatment while still involving the people closest to them as providers of support to increase patient optimism.